Assessment of rainwater harvesting systems at a university in Taipei. - Chiang, V. C.
Rainwater harvesting systems (RWHSs), a pilot-scale one (PSR) and a full-scale one (FSR), at a university campus in Taipei were assessed. Characteristics of harvested rainwater were analyzed, including pH, electrical conductivity (EC), turbidity, alkalinity, dissolved organic carbon (DOC), total coliform (TC), concentration of 14 metals (Al, Ca, K, Mg, Na, Cu, Fe, Mn, V, Zn, Cd, Cr, Pb and Ni) and concentration of 3 anions (Cl−, SO42− and NO3−). Rainwater in the FSR had pH in the neutral range and high alkalinity, whereas those of the PSR were acidic and with low buffer ability because of different catchment materials. Median concentrations of 14 metals from two RWHSs were low, except for Na, Ca, K and Mg. Anions, including Cl−, NO3−, and SO42− showed much higher concentration in winter, indicating the influences of marine source and northeast monsoon. Effects of 14-day storage were examined and it was found that pH did not change, while EC, turbidity and DOC slightly decreased. Concentrations of anions and metals were stable, and TC counts of harvested rainwater increased in the beginning, and then declined with storage time. During antecedent dry days, total suspended particulates (TSPs) were collected and their dissolution was examined. Preliminary correlation of wet and dry depositions with rainwater quality was explored.
Keywords: Acid precipitation; Dry deposition; Metals; Rainwater harvesting; Storage; Total suspended particulates (TSPs).